Improving Student’s Critical Thinking Ability Using HOTS-Based Modules in Chemistry Learning - Sugiharti, Gulmah; Siregar, Muhammad Isa; Samosir, Desima; Anugrah, Ade Nur (Journal of Ecohumanism, 2024)
Learning the 21st century obliges student For have three Skills that is Skills think critical, skills think creativity and skills solve problem. Skills the known with Skills think level tall or HOTS (Higher Order Thinking Skill). Study This aim to: (1) know appropriateness module HOTS based on the material acid-base in accordance with criteria that have been determined by BSNP. (2) knowing is ability think critical student use module HOTS based more tall rather than ability think student use book packages at school and. (3) knowing response student to module HOTS based on the material acids and bases that have been developed. This study made with Research & Development approach using ADDIE model paradigm. Study This conducted at Medan State University and Medan 21 State High School. Research result This show that through development module HOTS based on the material average acid-base result analysis is 91% (valid) and no need revised while the average response student is 85% (very interesting ). This matter show that module HOTS based on the material solution sour developed language​ worthy and very interesting for student . And the average value ability think critical student use developed module​ is 81 while the average value ability think critical student use book package at school of 70.8. This matter show ability think critical student use module Based on developed HOTS more tall compared to ability think critical student use book package at school.